Experiments on the collapse response of flat slab structures subjected to column loss. Issue 5 (6th March 2018) - Cuong, Tran Quoc; Linh, Nguyen Ngoc; Hung, Ha Manh; Hieu, Nguyen Trung; Dat, Pham Xuan
Abstract : Flat slab structures are prone to progressive collapse due to their relatively heavy self-weight and susceptibility to punching shear failure. In this study, three one-third scaled slab–column sub-assemblages were statically and dynamically tested to examine the collapse behaviour of such structures when either an edge or a penultimate column is removed. In the static tests, the development of an alternative load path bridging over the removed column was investigated with two specimens that were loaded to failure by a load-control procedure using concrete weights. In the dynamic test, a specimen that had been loaded by concrete weight up to 80% of the yield-line capacity was subjected to a sudden column removal, which was simulated by a quick-release mechanism. Based on the experimental observations, the potential failure modes of flat slab structures, the development of tensile membrane action as an alternative load path, and the dynamic effects resulting from sudden column removal are discussed.